2002
DOI: 10.1185/030079902125000444
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E Polymorphism with Myocardial Infarction in Greek Patients with Coronary Artery Disease

Abstract: Studies in several populations have indicated that genetic variation at the apolipoprotein E (apoE) structural locus influences the risk of coronary artery disease (CAD) and myocardial infarction (MI). This study aimed at investigating whether apoE polymorphism has an allelic and/or genotypic impact on the risk of MI in Greek patients with CAD. We compared apoE gene polymorphism in a group of patients with angiographically confirmed CAD but not MI [CAD/MI (-)-group, n = 143] and a group of age and sex-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 44 publications
2
42
0
1
Order By: Relevance
“…With regards to this, a recent study showed that the levels of Aβ oligomers in AD patients were lowest in those carrying the ε2-allele (Hashimoto et al, 2012). The ε2-allele also seems to play a protective role against CVD (Bennet et al, 2007;Gerdes et al, 2000;Kolovou et al, 2002), though the evidence is probably weaker than for negative effect of the ε4-allele (Drenos and Kirkwood, 2010). In addition, previous large population-based longitudinal studies, i.e., the Rotterdam study (Slooter et al, 2001) and the Danish 1905 birth cohort (Lindahl-Jacobsen et al, 2013) reported no favorable effect of ε2-allele on mortality in the elderly, despite protecting against cognitive decline in the oldest old (≥93 years) (Lindahl-Jacobsen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to this, a recent study showed that the levels of Aβ oligomers in AD patients were lowest in those carrying the ε2-allele (Hashimoto et al, 2012). The ε2-allele also seems to play a protective role against CVD (Bennet et al, 2007;Gerdes et al, 2000;Kolovou et al, 2002), though the evidence is probably weaker than for negative effect of the ε4-allele (Drenos and Kirkwood, 2010). In addition, previous large population-based longitudinal studies, i.e., the Rotterdam study (Slooter et al, 2001) and the Danish 1905 birth cohort (Lindahl-Jacobsen et al, 2013) reported no favorable effect of ε2-allele on mortality in the elderly, despite protecting against cognitive decline in the oldest old (≥93 years) (Lindahl-Jacobsen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] In our study, almost all patients carrying the e4 allele had an abnormal myocardial perfusion SPECT (SSS42). The subjects with ApoE E3/E3 and E3/E4 genotypes were prevalent (86.8%) among those with moderately and severely abnormal SPECT study (SSSX9).…”
Section: Discussionmentioning
confidence: 55%
“…Different result were found in China, where polymorphism of ε4 gene was not the risk factor for CHD (Liu et al, 2003), as well as in coronary artery disease. This ε4 gene was not the risk factor in Oman, Greek and Brazalian populations (Al-Yahyaee et al, 2007;De Franca et al, 2004;Kolovou et al, 2002;Souza et al, 2007) The role of apoE polymorphism in causing dyslipidemia was studied in CHD patients and controls. Apolipoprotein ε2 allele has protective effect for CHD, but ε3 and ε4 alleles were the risk factor for CHD especially in individuals with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%